Pembangunan Sistem Market Place Pada Konveksi Berbasis Web (Studi Kasus Konveksi Nine-Clothing dan The Rop) - Muhammad Fadel; Fajar Pradana; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Convection is a business that is engaged in the manufacture of clothing or textiles managed by individuals with an order scale of under 500 pieces. Convection performs the production process when there are orders and does not perform when there are no orders, also does not produce the clothes themselves to be traded. In general, the developed system has four important processes as solutions to existing problems. The important process includes direct design in system by consumer, negotiation process between consumer and convection, production process which consumer can monitoring the process by update from convection, and accumulation of production and turnover which convection can monitoring it. In the system development phase, the model used is to use SDLC Waterfall. The developed system consists of 38 functional requirements that are divided into two different actors. In developing the thesis system, several supporting technologies are used to make it easier to work. Supporting technologies used include MySQL Database Management System, PHP Programming Language, and PHP Laravel Framework. The process of developing system is divided into several structural phases which form the basis of this thesis research method. These phases consist of requirements analysis, system design and implementation, to testing. Testing method in this research are used white box testing method at the unit testing and integration stage, and black box testing is used in the validation testing stage. System testing carried out has overall valid results on the test cases that have been made. The test case created is based on the previous stage, namely the needs analysis and system design.